Collapse prognosis of a long‐span cable‐stayed bridge based on shake table test and nonlinear model updating - Lin, Kaiqi; Xu, You‐Lin; Lu, Xinzheng; Guan, Zhongguo; Li, Jianzhong (Earthquake engineering & structural dynamics, 2021)
Summary The collapse of long‐span cable‐stayed bridges under strong earthquakes will not only result in severe casualties and loss of property but also significantly delay the rehabilitation of the affected area. It is therefore essential to study the failure progress and potential collapse mechanisms of these bridges under strong earthquakes for assisting their inspection and maintenance and helping them survive an earthquake. Collapse simulations in existing studies are commonly conducted with design‐document‐based finite element (FE) models, which usually neglect the actual damage state of the bridges. The influences of modelling uncertainties on the simulated responses cannot be addressed. This study proposes a nonlinear FE model updating‐based collapse prognosis method for long‐span cable‐stayed bridges, which includes (1) a correlated‐updating‐parameter‐based nonlinear FE model updating algorithm, (2) a restarted time history analysis‐based seismic response prediction method and (3) an elemental deactivation‐based collapse simulation algorithm. The shake table test of a scaled Sutong cable‐stayed bridge in China is adopted to illustrate the proposed earthquake‐induced collapse prognosis method. A refined FE model of the bridge is first established and nonlinearly updated using the measurement data. The collapse prognosis of the bridge under a subsequent strong ground motion is then performed based on the updated model. The predicted structural responses and final failure mechanisms are compared with the measured responses and experimental observations with good agreement, indicating that the proposed method is feasible and accurate for evaluating the seismic performance and failure mechanisms of long‐span cable‐stayed bridges.